PERSEPSIS SISWA SEKOLAH DASAR TENTANG LINGKUNGAN HIDUP - Bahij, Azmi Al; Santi, Apri Utami Parta (Universitas Muhammadiyah Jakarta, 2017)
By promoting student with positive perception, it can effectively increase their awareness and understanding in crating the goog environmental education in school. Adiwiyata green school program implemented in order to bring the school community around who are responsible for caring school as the learning environment. The study was conductedapril 2016 to the november 2016. The purpose of this study was to know the differences students’ perceptions about environment both of elementary schools at muhammadiyah 12 pamulang and labs school FIP UMJ. The method used in the reserch is a quantitative descriptive survey approch. Data ware first analyzed with analyzed descriptive techniques. The researchers then used cross tabulation as the next step analysis in order to determine the differencesamong students’perceptions. Furthermore, to find out whether the school status will has an influences on students’ environment student perceptions or not, was examined by non parametric Mann Whitney U . by taking cross tabulation analysis, know the differences students’ perception about environment both elementary school at muhammadiyah 12 pamulang and labs school FIP UMJ explicitly could be know. Based on mann Whitney U test, it was reported that that the value of asymp sig (2 tailed)was 0.453 > 0.05, the test indicated that there was no significantly influences between adiwiyata school and non adiwiyata schoolin students’ perception obout environment.